Escherichia coli as a Tool for Disease Risk Assessment of Drinking Water Sources - Stephen T. Odonkor; Tahiru Mahami (International Journal of Microbiology)
Many diseases have been associated with poor drinking water quality including diseases caused by diarrheagenic pathogens, especially in developing countries where access to a consistent water supply is a problem. The objective of the study was to evaluate the health risks associated with the sources of drinking water in the Dangme West District of Ghana using E. coli as a measurement tool, aiming at ascertaining the paths leading to contamination of the water sources. A total of 464 water samples were obtained for analysis. Sampling covered a year across the dry and wet seasons in Ghana. Water samples were obtained from groundwater and surface water sources. E. coli counts were determined using the most probable number method (MPN). Disease risk assessment was carried out using the WHO drinking water risk assessment guidelines. Generally, the study revealed significantly higher E. coli counts in the wet season than in the dry season. Among the water samples analyzed, surface water, especially from the dams, was found to pose the highest disease risk as compared to the other water sources. Samples from groundwater sources, especially boreholes, posed the lowest disease risk. In conclusion, observations from the study implied that most water sources in the study district are highly polluted with bacteria pathogens beyond recommended safety guidelines. The main causes of faecal contamination in these water sources were purported to be anthropogenic. Therefore, there is a need to formulate a policy aimed at managing and improving rural water sources.